Analysis of The Effect of Temperature Variations and Natural Gas Flow on Zinc Oxide (Zno) Quality Results Using The French Method - Suyadi, Yadi; Alva, Sagir (Universitas Mercu Buana, 2025)
This study aims to analyze the effect of temperature and gas flow variations on the quality of Zinc Oxide (ZnO) produced in terms of particle size and product purity using the French method. The French method is a standard production technique used to manufacture ZnO, which utilizes the oxidation of zinc metal at high temperatures. The problem in the ZnO manufacturing process is determining what natural gas temperature and flow will be used to obtain the best quality, considering fuel consumption and production efficiency. In this study, temperature variations of 900°C, 1000°C, and 1100°C and natural gas flow using CNG (Compressed Natural Gas) with variations of 50 m3/hour, 55m3/hour, 60m3/hour were applied to understand how these parameters affect the properties of the resulting ZnO, characterization of the results was carried out using the complexometric titration method with ethylenediaminetetraacetic acid (EDTA) solution to determine the purity of the resulting ZnO and using a laser diffraction instrument to examine the size of ZnO particles. The results showed that the process temperature significantly affected the purity of ZnO. At a temperature of 1100 °C, the purity of ZnO reached 99.94%, which is the testing value in this study. At a gas flow of 60 m3/h, the purity of ZnO tends to be stable at a value of 99.93–99.94%. Meanwhile, the results of particle measurements at a temperature of 900°C with a gas flow of 50 m3/h, D50 reached 1.235 µm. At a temperature of 1100°C with a gas flow of 60 m3/h, D50 decreased to 1.089 µm. This particle size indicates that high temperatures encourage agglomeration reduction, resulting in finer ZnO particles. This study concludes that temperature and gas flow parameters play an important role in controlling the quality of ZnO produced through the method, with oxygen gas flow at high temperatures giving optimal results.